2022
DOI: 10.1007/s10734-022-00834-8
|View full text |Cite
|
Sign up to set email alerts
|

Constructing radical community: an ecological model for shifting from an EdD to a We-dD in online doctoral programs

Abstract: Online learning is often associated with the alone together paradox that suggests that online students are constantly connected to one another yet feel more alone due to a lack of real social connection. While research has approached this issue from an environmental perspective, some scholars have recently suggested that aspects of online students’ complex ecologies, beyond the online program, may also influence the degree students engage socially. This phenomenological study explores th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It was found that the broader working culture in academia permeated other, more proximal layers within the students’ environment, impacting their mental health and wellbeing (Jackman et al, 2022). Similarly, the feelings of isolation in an online EdD program went beyond the immediate elements within a program environment, but was subject to outside factors that either enhance or detract students from social engagement (Graham et al, 2023). Despite these studies lending empirical weight to the validity and perspicacity of exploring doctoral students via an ecological lens, no study has yet cast an ecological light on Chinese VDS’ emic perception of the non-degree mobility experience, thus leaving a gap for this research to fill.…”
Section: Theoretical Underpinning: Doctoral Education Via An Ecologic...mentioning
confidence: 99%
“…It was found that the broader working culture in academia permeated other, more proximal layers within the students’ environment, impacting their mental health and wellbeing (Jackman et al, 2022). Similarly, the feelings of isolation in an online EdD program went beyond the immediate elements within a program environment, but was subject to outside factors that either enhance or detract students from social engagement (Graham et al, 2023). Despite these studies lending empirical weight to the validity and perspicacity of exploring doctoral students via an ecological lens, no study has yet cast an ecological light on Chinese VDS’ emic perception of the non-degree mobility experience, thus leaving a gap for this research to fill.…”
Section: Theoretical Underpinning: Doctoral Education Via An Ecologic...mentioning
confidence: 99%
“…Nascent research on distance doctoral students' conception of belonging confirms this statement: a qualitative study of the experiences of one online student who lived in Iraq and was attending a PhD program indicated she felt a sense of belonging "to some extent" [43] (p. 5) due to connections with supervisors and peers through WhatsApp, Twitter, and/or other virtual platforms [43]. Other studies of online doctoral programs point to program elements, such as a cohort model and informal online spaces, which promote belonging [44]. Our study provides quantitative evidence that a moderate sense of belonging is possible in online doctoral education.…”
Section: Process Of Becoming Academic Writersmentioning
confidence: 99%